DISTRIBUSI ALAT PELINDUNG DIRI PADA MASA AWAL PANDEMI COVID-19 DI KALIMANTAN BARAT - Wicaksono, Arif; Nurfianti, Arina; Desnita, Rise; Andriani, Andriani (Jurnal Pengabdian Masyarakat Trimedika, 2026)
Coronavirus Disease 2019 (COVID-19) pandemic had affected many sectors, especially health sector. Health workers must wear Personal Protective Equipment (PPE) in several levels according to the risk they will face. Personal Protective Equipment such as face mask, hand glove, surgical gown and boots are the most common PPE used in the pandemic. Personal Protective Equipment should be used mainly for health workers. The community was not well-informed so there were panic buying of PPE and risen scarcity of PPE. Scarcity of PPE happened in early pandemic in every region including West Kalimantan. Faculty of Medicine Universitas Tanjungpura gather PPE donation to health facilities in West Kalimantan. The donation collected and distributed to 15 health facilities. The donations got positive feedback and the facilites stated that the health services in their facilities was helped considerably